2015
DOI: 10.1002/acn3.183
|View full text |Cite
|
Sign up to set email alerts
|

Methionine increases BDNF DNA methylation and improves memory in epilepsy

Abstract: ObjectiveTemporal lobe epilepsy (TLE) patients exhibit signs of memory impairments even when seizures are pharmacologically controlled. Surprisingly, the underlying molecular mechanisms involved in TLE-associated memory impairments remain elusive. Memory consolidation requires epigenetic transcriptional regulation of genes in the hippocampus; therefore, we aimed to determine how epigenetic DNA methylation mechanisms affect learning-induced transcription of memory-permissive genes in the epileptic hippocampus.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…Our finding of no alterations in global DNA methylation levels might be a result of the fact that central levels of the other measured 1‐CMAM are unaffected by ES. These are further supported by evidence that both maternal care and acute methionine administration in a model of epilepsy failed to alter global DNA methylation in the hippocampus (12, 52).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our finding of no alterations in global DNA methylation levels might be a result of the fact that central levels of the other measured 1‐CMAM are unaffected by ES. These are further supported by evidence that both maternal care and acute methionine administration in a model of epilepsy failed to alter global DNA methylation in the hippocampus (12, 52).…”
Section: Discussionmentioning
confidence: 70%
“…Of interest, effects of methionine supplementation during adulthood have been reported before, although these were administered for a prolonged period of time under depletion conditions‐for instance, severe adult folate deficiency induced cognitive impairments that could be prevented by a prolonged dietary methionine supplementation (47). In addition, also highlighting the powerful properties of these nutrients under specific conditions, acute or prolonged administration of methionine or the universal methyl donor S‐adenosyl methionine during adulthood rescued cognitive impairments that were a result of earlier epilepsy or lead or cocaine exposure (12, 4852) and improved drug‐seeking behaviors (53). Our results show the sensitivity of specific nutrients to ES exposure and highlight a key role for them during early life in long‐term brain programming, as well as the efficacy of early nutritional interventions to prevent later ES‐induced effects on cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously reported a significant decrease in hippocampal BDNF expression in the same rat model of 3-hour daily maternal separation [44]. A recent study has reported that methyl supplementation via methionine is able to increase BDNF DNA methylation and reduce BDNF mRNA levels in the hippocampus of epileptic rats during memory consolidation, reversing memory deficits in these animals [45]. This result suggests that methyl donor supplementation as performed in our study (extra folic acid, vitamin B12, betaine and choline) could also be able to reverse the detrimental effects of early life stress on BDNF methylation and expression in rat hippocampus, although more studies are required.…”
Section: Discussionmentioning
confidence: 79%
“…DNA methylation is one factor that involved in epigenetic modulation and tends to silence genes [43]. In the current study, we assessed DNA methylation levels in the exon IV of BDNF transcripts based on the fact that exon IV is the primary BDNF exon responsible for activity-dependent BDNF mRNA expression [44][45][46]. As well, it is known that environment-induced changes in BDNF gene expression correlated with DNA methylation of exon IV.…”
Section: Discussionmentioning
confidence: 99%